Radiocapitellar joint plasty for missed monteggia fracture with radial head deformity in children: a retrospective study - Li, Xuedong; Tian, Huiling; Lu, Kun; Jing, Xiaobo (Frontiers in Pediatrics, 2024)
Purpose: The retrospective study reviewed the clinical and radiological outcomes of patients treated with radiocapitellar joint plasty. Methods: 10 children with missed Monteggia fracture (MMF) were reviewed. The average time from injury to operation was 20 months. The average age of children who underwent the operation was 10.5 years. 6 flat and 4 domed radial heads were included. 7 type I and 3 type III MMF were identified based on the Bado classification. All children with MMF were treated by open radial head reduction with radiocapitellar joint plasty and ulnar osteotomy (UO).The average union time was 4.9 ± 2.6 months. The average osteotomy angle to reduce the radial head was 15.7 ± 3.5°, and the average lengthening of the ulna was 8.2± 3.2 mm. The average preoperative flexion range of motion was110.5 ± 9.1°, and the postoperative flexion range of motion was 138.8 ± 15.1° (p < 0.05). The average preoperative extension range of motion was 10.1 ± 3.2°, and the postoperative extension range of motion was 5.5 ± 3.3° (p <0 .05). The average preoperative pronation range of motion was 78.8 ± 8.7°, while the postoperative pronation range of motion was 81.1 ± 5.6° (p > 0.05). The average preoperative supination range of motion was 68.3 ± 9.7°, and the postoperative supination range of motion was 80.1 ± 7.8° (p < 0.05). The preoperative Kim score was 66.5 ± 10.9°, and the postoperative Kim score was 88.1 ± 12.6 (p < 0.05). The radial head was completely reduced in 9 patients, and subluxation in 1 patient. Osteoarthritis of the radiocapitellar joint was observed in 2 patients.Conclusions: Radiocapitellar joint plasty is effective surgical intervention for MMF with radial head deformity. It yields favorable functional outcomes while ensuring continued radial head reduction.